2006
DOI: 10.1007/s00244-005-1097-1
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Distribution, and Characterization of Suspected Endocrine-Disrupting Pesticides in Beijing GuanTing Reservoir (GTR)

Abstract: Abstract. GuanTing Reservoir (GTR) is one of two main water resources for the agriculture, industry, and living uses of Beijing (China). As a result of extensive pollution over the last few decades (particularly the 1980s), the reservoir has not supplied potable water to Beijing city since 1997. Composition, distribution, and characterization of 31 suspected endocrine-disrupting pesticides in surface water, pore water, and surface sediments from the reservoir are reported in this study. An analytical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…And DDTs production also continued due to export demand and dicofol production after the restriction of technical HCHs and DDTs in 1983 [9][10][11]. Extensive and continuous use of OCPs in China has resulted in ubiquitous OCPs pollution in various environmental media, especially in sediments [2,3,[12][13][14][15]. Recently levels and distributions of OCPs in sediments have frequently been detected [4,12,16,17].…”
Section: Introductionmentioning
confidence: 96%
“…And DDTs production also continued due to export demand and dicofol production after the restriction of technical HCHs and DDTs in 1983 [9][10][11]. Extensive and continuous use of OCPs in China has resulted in ubiquitous OCPs pollution in various environmental media, especially in sediments [2,3,[12][13][14][15]. Recently levels and distributions of OCPs in sediments have frequently been detected [4,12,16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Due to their intensive utilization in agricultural and industrial activities, reported across the world, even in Antarctica and the Arctic Zone (Fu et al 2001;Chiuchiolo et al 2004;Li and Macdonald 2005). Moreover, a majority of these pesticides belongs to endocrine-disrupting chemicals (Xue and Xu 2006), which have been well proved as a series of most harmful substances to the endocrine system of human beings and wild animals. Since these chemicals pose great threats to the health of ecosystem and human beings and have become one of the prevalent environmental issues across the world, it would be desirable and imperative to investigate their fates and transports in natural environment especially for countries with large-scale of OCPs adoptions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that EDCs can be detected in most of China's surface drinking water sources. The predominant species are organochlorine pesticides, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and phthalic acid esters (PAEs) or phthalates (Na et al, 2006; Qian et al, 2006; Sun et al, 2006; Xue and Xu, 2006; Zhou et al, 2006) Many studies suggested that source water and even drinking water in China have been polluted by organic pollutants. It was reported that di‐ n ‐butyl phthalate (DBP) and di‐(2‐ethylhexyl) phthalate were the main pollutants among five PAEs studied in the Wuhan section of the Yangtze River in high and low water periods, exceeding the Surface Water Quality Criteria of China by 82.4% (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%